Redefining Adaptation Studies. - Cutchins, Dennis R. (Dennis Ray), 1963-; Raw, Laurence; Welsh, James M., 1938-2013 (Rowman & Littlefield Pub. Group, 2010)
Since films were first produced, adapted works have predominantly borrowed primarily from traditional texts, such as novels and plays. Likewise, the study of film adaptations has also been fairly traditional, rarely venturing beyond a comparison of the source material to its often less revered counterpart. Redefining Adaptation Studies breaks new ground in showing the range of possibilities that transcend the literature/film paradigm. These essays focus on the idea of 'adaptation' and what it meansin different socio-political contexts. Above all this collection shows how cultural and political.